AKTIVITAS PETANI DI DESA TOMPASOBARU DUA KECAMATAN TOMPASOBARU KABUPATEN MINAHASA SELATAN (Farming Activities in Tompasobaru Dua Village, Tompasobaru Sub-District, South Minahasa Regency) - Victory Langoy; Mex F. L. Sondakh; O. Esry H. Laoh (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
This study aims to determine the daily activities of farmers in Tompasobaru Dua Village, Tompasobaru District, South Minahasa Regency. The study was conducted during June-August 2022, starting from preparation to data collection in Tompasobaru Dua Village, Tompasobaru Dis-trict. The data used in this study were primary and secondary data. Primary data were obtained through direct interviews with farmers in Tompasobaru Dua Village using a questionnaire. Mean-while, secondary data were taken from the village government of Tompasobaru Dua, analyzed using interval tables and described. The results of this study indicate that the activities of farmers in Tompasobaru Dua Village are divided into three types: agricultural activities, social activities, and religious activities. In the initial agricultural activity, farmers spend 48 hours per week and 96 hours per month. Maintenance activities require 48 hours per week and 144 hours per month. Harvesting activities require 48 hours per week and 96 hours per month. On average, farmers spend 45 hours per week on agricultural activities. In social activities, farmers spend an average of 7 hours per week, while in religious activities, they spend an average of 2.5 hours per week.Farmers in Tompasobaru Dua Village should maintain their working hours in agricultural ac-tivities to achieve better results than before. For social activities, farmers should utilize their availa-ble time and increase their social activities in life as social beings. For religious activities, farmers should maintain their spiritual attitudes to always participate in existing religious activities.